Using the Totipotency Abilities of Plants in Plant Breeding: Tissue Culture Techniques - İsmail Karakaş (Acta Natura et Scientia)
Some of the biotechnological methods have been successfully applied in cultivated plants after the 1980s and have become practical by being included in the agricultural systems of many countries around the world. Totipotency in plant tissue culture; It can be defined as the ability to produce a completely new plant from a living plant cell. Theoretically, it is possible to grow completely new plants from root, leaf, pollen and petal cells. Plant tissue culture The in vitro aseptic culture of cells, tissues, organs and their components under defined physical and chemical conditions is an important tool in both basic and applied studies and commercial application. The combination of classical and biotechnological methods in plant breeding programs has ample potential to produce plants of superior quality and better disease tolerance and stress tolerance capacities, selection of useful variants in well-adapted high yielding genotypes. As a tool that provides significant opportunities for plant quality improvement and economic sustainability, plant tissue culture has reduced the time and workforce in plant breeding programs.